Potential Benefits of Playing Location-based Games: An Analysis of Game Mechanics - Laato Samuli; Pietarinen Tarja; Rauti Sampsa; Sutinen Erkki (Switzerland, 2022)
Abstract. Previous studies have reported various potential benefits from playing location-based games (LBGs). These include being outdoors, exercise, decreased sedentary behavior, increased knowledge of surroundings, improved cartographic, geographical and navigation skills, increased social interaction, meeting new people, forming acquaintances and activating people. One of the benefits of LBGs is that compared to other self-help applications and games, they are able to reach demographics who have trouble or are not interested in seeking improvement in their lives. This study focuses on the currently available LBGs (N=60) and identifies how their gameplay supports the observed benefits of playing the games. The found LBGs were sorted into five sub-genres. At the core of the popular LBGs Pok´emon GO and Harry Potter: Wizards Unite were three main game mechanics all supporting each other: (1) moving around to find points of interest (PoIs), (2) travelling to PoIs and (3) walking to trigger game-events. Most gameplay were tied to these, as were also the potential benefits of playing the games. These findings highlight the importance of PoIs, their location and their quality, for maximizing the benefits gained from playing LBGs. Keywords: Location-based games · gameplay · game mechanics · Pok´emon GO · potential benefits
Computer Supported Education: 11th International Conference, CSEDU 2019, Heraklion, Crete, Greece, May 2-4, 2019, Revised Selected Papers